Concept Analysis of the Neuro-ischaemic Phenotype: Integrating Diabetic Peripheral Neuropathy and Peripheral Artery Disease for Diabetic Foot Ulcer Risk Stratification - Burhan, Asmat; Susanti, Indah (Java Nursing Journal, 2026)
Background: Diabetic foot disease remains a major cause of ulceration and amputation, yet neuropathy and peripheral arterial disease are often assessed separately, limiting consistent identification of neuro-ischaemic risk. Purpose: To analyze the concept of the neuro-ischaemic phenotype in diabetic foot ulceration based on the method introduced by Walker and Avant Methods: In a Walker and Avant concept analysis of published literature from PubMed, Embase, Scopus, and Web of Science from November 2020 to 2025, we extracted concept uses, defining attributes, antecedents, consequences, and empirical referents for neuro-ischemic DFU. Boundaries were refined using model, borderline, related, and contrary cases, then synthesised into an operational framework. Results: The analysis defined the phenotype as coexisting loss of protective sensation and objectively confirmed lower-limb ischaemia. Five defining attributes were identified, including silent progression and the need for dual-domain measurement. A tiered minimum dataset was proposed, utilizing the ankle-brachial index, toe-based measures, and Doppler waveform, to reduce misclassification and guide escalation pathways. Conclusion: An integrated neuro-ischaemic phenotype closes single-domain gaps and enables standardised DFU risk stratification. It supports nursing-led triage and referral pathways and requires prospective validation for clinical outcomes. Relevance to clinical practice: Neuro-ischaemic DFU triage: nurses pair Loss of Protective Sensation (LOPS) screening with perfusion tests (ABI plus toe indices or Doppler) to stratify risk, speed early vascular review, tailor offloading/infection surveillance, and standardise communication.